Pencak Silat Sebagai Solusi Pencegahan Kekerasan Seksual Pada Anak Tunarungu - Ilahi, Rahmat; Temmassonge, Andi; Haris, Iyan Nurdiyan; Santos, Maria Herlinda Dos; Adriana, Adriana (Penerbit Widina, Widina Media Utama, 2025)
Sexual violence is a crime that often occurs both in public and domestically. The service activities were carried out in three meetings, namely, first, conducting observations to see the problems and solutions that would be offered, second, holding seminars to increase students' and teachers' knowledge about sexual violence and pencak silat martial arts, third, implementing pencak silat practices in the prevention of sexual violence against children with special disabilities for deaf children. The implementation of this service activity went well, all because of the help and encouragement from the parties involved and we as the service team would like to say thank you very much. Measuring the success of the program by conducting interviews. The results of the final interview were that students began to have the courage to defend themselves when they received sexual violence from their friends. Entrust one of the teachers to be a pencak silat martial arts trainer using movements according to the book that has been created.ABSTRAKKekerasan seksual merupakan kejahatan yang kerap terjadi baik di publik maupun domestik. Kegiatan pengabdian dilakukan tiga kali pertemuan, yakni pertama melakukan observasi untuk melihat masalah dan solusi yang akan ditawarkan, kedua melaksanakan seminar untuk meningkatkan pengetahuan siswa dan guru tentang kekerasan seksual dan bela diri pencak silat, ketiga pelaksanaan praktik pencak silat dalam upaya pencegahan kekerasan seksual anak disabilitas khusus anak tunarungu. Keterlaksanaan kegiatan pengabdian ini berjalan dengan baik, semua itu karena bantuan dan dorongan dari pihak-pihak yang terlibat dan kami selaku tim pengabdian mengucapkan banyak terima kasih. Mengukur keberhasilan program dengan mengadakan wawancara. Adapun hasil wawancara terakhir yang dilakukan adalah siswa mulai berani melakukan pembelaan diri ketika mendapatkan kekerasan seksual dari temannya. Mempercayakan salah satu guru untuk menjadi pelatih bela diri pencak silat dengan menggunakan gerakan-gerakan sesuai dengan buku yang telah dibuat.